Building information modeling to support facilities management of large capital projects: a critical review. Issue 3 (6th October 2021) - Asare, Kofi Asabere Bediako; Liu, Rui; Anumba, Chimay J.
Abstract : Purpose: This paper aims to present a review of research developments relating to the application of building information modeling (BIM) to facilities management (FM). It sheds light on major technical and organizational issues with the view of identifying how existing BIM for FM knowledge applies to large capital projects. Design/methodology/approach: The study adopted a literature search approach to retrieve relevant articles which were subjected to keyword analysis to enable categorization of extant BIM for FM research into appropriate sub-domains. A qualitative analysis of 94 BIM for FM-related literature was carried out in addition to a review of 9 capital project-related articles, leading to the establishment of research trends, gaps and future directions. Findings: The review found that research in the BIM-FM integration field is predominantly technology and process-oriented, with less attention paid to people or organizational aspects. Therefore, there is a need for expanding the knowledge base in this direction. Several future research directions were identified to lay the foundations for research on BIM application to FM in large capital projects and other application areas for interested researchers. These future directions were categorized under the identified sub-domains of the field and mapped onto two generic activities, i.e. technical integration and business integration, involved in technology adoption by organizations. Originality/value: The main contribution of this study is the categorization of existing research on BIM for FM, leading to the identification of research gaps concerning the initiation and implementation of BIM for FM in large capital projects. As a secondary benefit, this study has validated some sub-domains of the BIM for the FM research field identified in previous review papers using an empirical approach. This validation of defined sub-domains is useful for an emerging research field as it provides a common understanding of trends and specific application areas.